PATHOLOGICAL ASSESSMENT OF LIVER EXPLANT IN PROLONGED ISCHEMIA USING THE COMBINED METHOD OF CONSERVATION IN THE EXPERIMENT - Сохарев, Анатолий Сергеевич; Краснов, Константин Аркадьевич; Будаев, Алексей Владимирович; Плотникова, Екатерина Юрьевна; Шрайбер, Станислав Александрович (Medicine in Kuzbass, 2016)
Objective – to evaluate the efficacy of ischemic protection of the combined solution based on the HTK (histidine-tryptophan-ketoglutarate) and NEPFOS (not oxygenated perfluororganic solution) in the liver explant conservation.Materials and methods. We performed a study on 60 rabbits. For histology and morphometry the biopsy of rabbit liver was performed before the conservation and in 8 hours after the conservation in different preservative solutions. Histological and morphometric studies numbered 240.Results. In 8-hour conservation of liver explants using the combined solution based on HTK and NEPFOS less severe ischemic changes in liver tissue structures have developed compared to monopreservative solutions: standard HTK and control NEPFOS. Therefore, the combined method of conservation reduces the intensity of ischemic injury of the liver explant and thereby increases its vitality, it being the necessary condition for reducing the risk of possible post-transplant complications.Conclusions. The use of the combined method of conservation can minimize pathological changes in the explant tissues and prevent ischemic liver injury.
Keywords: liver conservation; ischemic liver injury; not oxygenated perfluororganic solution